Evaluation of Curcumin Effect in Diabetes and Diabetic Atherosclerosis - Ali Shoja, Nafiseh Nasri-Nasrabadi, Mojtaba Hajihoseini, Ramin Ataee, Amin Ataie (International Journal of Innovative Research in Medical Science, 2017)
Background: Curcumin is an herbal constitute from curcuma lunga. The root of curcuma has been known for its antioxidant properties with benefical effects in diabetes and atherosclerosis. Also there are some reports about its antioxidative stress properties. According to this background, we have prepared this minireview considering 20-30 recent articles. Materials and Methods: We have accumulated 23orginaland review articles from Medical Database Publication Science, Scopus, Google scholar, web of Sience and Elsevier about role of curcumin and in diabetes and atherosclerosis. Results: According to these studies, curcumine through intervention in decreasing serum fatty acid (due to increased consumption of fatty acid oxidation) can reduce glucose in patients with diabetes. Also by improving pancreatic beta cell function as pre-diabetes intervention is benifical too. Alsocurcumin by reducing the pulse wave velocity, leptin levels, triglycerides, uric acid, visceral fat and total body fat as well as increased levels of adiponectin in diabetes patients can reduce the risk of atherosclerosis. Conclusion: According to these results we can introduce curcumin for co-treatments in diabetic patients especially who are at risk of atherosclerosis.